THE EFFECT OF N FERTILIZER WITH MEDIA AND PLANTING ROWS IN VERTICULTURE CULTIVATION OF VERTIGATION SYSTEM ON PAKCOY PLANTS IN DRY LAND - Neonbasu, Noventus Be; Tobing, Wilda Lumban (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Cultivation in dry land requires heavy management because it has a fairly low physical quality. The verticulture system with fertigation is an innovation in dryland cultivation that can increase pakchoi production. The purpose of this study was to examine the effect of the combination of N fertilizer with media formulation and planting rows in verticulture on pakchoi in dryland. This study used an experimental method with a Split Plot Design. The main plots of media and fertilizers consisted of: a combination of 50% soil planting media: biochar + 50% compost with 1 g/L urea + 40 mL/L POC + 10 mL/L BPN; a combination of 50% soil planting media: biochar + 50% compost with 0.75 g/L urea + 30 mL/L POC + 7.5 mL/L BPN; a combination of 25% soil planting media: biochar + 75% compost with 1 g/L urea fertilizer + 40 mL/L POC + 10 mL/L BPN; a combination of 25% soil planting media: biochar + 75% compost with 0.75 g/L urea + 30 mL/L POC + 7.5 mL/L BPN. The sub-plots consist of the first row; the second row; and the third row. The results showed that the combination of N fertilizer with the media formulation and rows was able to increase the growth and yield of pakchoi plants with the best results being a combination of 25% soil planting media: biochar + 75% compost with 0.75 g/L urea + 30 mL/L POC + 7.5 mL/L BPN and the second row in verticulture using the fertigation system. Keywords: Biochar, Compost, Liquid Organic Fertilizer, Nitrogen Fixing Bacteria, Urea.